A Framework and Survey of Advanced Process Control Economic Evaluation: Assessing the Economic Benefits of Advanced Process Control (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Stabilizing the process operation is a major goal of commercial advanced control of processes(APC) programs. The advantages of implementing new APC technologies into a process must bemeasured economically so as to justify the expense involved. Previously, techniques for economicevaluation were created that connected changes in important regulated process variables to measures ofeconomic performance. In order to gather industry norms and recommendations, an investigation intothe current method of assessing APC's economic performance was conducted. The purpose of thequestionnaire was to determine methodologies for estimating economic performance and to assess theimpact of economic performance on the managerial process. The questionnaire was made available intwo somewhat different versions one for experts working for production firms (also known as APCusers) and another for specialists working for APC structure suppliers (sometimes called APCproviders). Process control engineers, managers, and creators of control technology were all a part ofthe target group. This study examines these techniques and applies them to an economic evaluationapproach for APC projects. 125 APC specialists from different industries were undertaken for evaluationregarding ROI of control of processes. The findings provide details on the evaluation of the financialadvantages of sophisticated process control.